2021
DOI: 10.3390/ijerph182312446
|View full text |Cite
|
Sign up to set email alerts
|

Application of Capacitive-Resistive Electric Transfer in Physiotherapeutic Clinical Practice and Sports

Abstract: Diathermy techniques embody an oscillating electrical current passaging through the body tissues generating therapeutic heat; use of this technique in the physiotherapy field has been introduced recently, and because there is scarce information, the following review is proposed, aiming to explore the available evidence on applying CRET in physiotherapy clinical practice and sports. A systematic search was led through a keyword search on PubMed, MedLine, DialNet, Scopus, PEDro, Web of Science and Clinicaltrials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
16
0
5
Order By: Relevance
“…Energy is transferred to the tissues in a capacitive way, by means of a single metal electrode, suitably shielded by insulating material. The second conductive plate of the capacitor is given by the body tissue, and this implies that the electromagnetic charge is concentrated near the isolated electrode, i.e., in the superficial tissues [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy is transferred to the tissues in a capacitive way, by means of a single metal electrode, suitably shielded by insulating material. The second conductive plate of the capacitor is given by the body tissue, and this implies that the electromagnetic charge is concentrated near the isolated electrode, i.e., in the superficial tissues [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The catabolic products are drained more quickly and the diapedesis of granulocytes, macrophages, and of the cells involved in inflammatory and reparative processes increases. In addition, the “cell killing” effect of senescent and damaged cells occurs [ 48 , 49 , 55 , 56 , 57 , 58 ]. The rise in temperature extends deeper [ 48 , 49 , 55 ], although the actual amount progressively decreases as it deepens from the surface of the skin [ 47 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the two electrodes are often used interchangeably during one procedure. Independent of the heating method, it is necessary to use a passive electrode, ensuring the closure of the electrical circuit [ 11 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding previous research on CRET and sports, a recent systematic review explored the use of this technology in the sports field [ 36 ], and identified only one study that assessed biomechanical changes in athletes and other physiological effects [ 37 ]. The review pointed out the lack of evidence for this technology’s potential in sports performance, and the need to address this gap [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding previous research on CRET and sports, a recent systematic review explored the use of this technology in the sports field [ 36 ], and identified only one study that assessed biomechanical changes in athletes and other physiological effects [ 37 ]. The review pointed out the lack of evidence for this technology’s potential in sports performance, and the need to address this gap [ 36 ]. No study has been carried to analyze the effects of this technology on variables for sports performance such as time trials or the Borg scale, and it has not been applied to the Paralympic population.…”
Section: Introductionmentioning
confidence: 99%